Polarizing plate with phase difference layer and image display device
By introducing a high elastic layer and an antistatic agent into the polarizer with a phase difference layer, the problem of iodine or antistatic agent flowing out at high temperature and high humidity is solved, and the durability of the image display device and the stability of the electrode are improved.
Patent Information
- Application Number
- CN202380040765.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-22
- Publication Date
- 2024-12-27
AI Technical Summary
In high temperature and high humidity environments, cracks may appear in polarizers with phase difference layers, causing iodine or antistatic agent to flow out, damage the image display panel and reduce its durability.
A polarizer with a phase difference layer is designed, which includes an adhesive layer containing an antistatic agent and a high elastic layer. By keeping the resistivity of the aluminum layer at 85% RH conditions of 110°C, the resistivity of the aluminum layer is reduced by 2 or less. Heat shrinkage and cracking are generated and provide sufficient antistatic function without substantially plasticizing the adhesive layer.
It effectively improves the durability of the image display device in high temperature and high humidity environments, prevents the outflow of iodine or antistatic agents, and reduces the corrosion of the electrode and the adverse effects caused by static electricity.
Smart Images

Figure CN119213339A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polarizing plate with a phase difference layer and an image display device. Background Art
[0002] In recent years, image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices (such as organic EL display devices and inorganic EL display devices) are rapidly becoming popular. In these image display devices, generally for the purpose of optical compensation and anti-reflection of external light, a polarizer with a phase difference layer formed by integrating a polarizer and a phase difference layer is widely used (Patent Document 1, etc.). For example, in an organic EL display device, a polarizer (circular polarizer) with a phase difference layer is arranged on the visible side of the organic EL panel to prevent the reflection of external light caused by the electrode arranged on the panel.
[0003] In addition, in polarizing plates with retardation layers disposed on the visible side of image display panels such as organic EL panels and liquid crystal panels, an antistatic agent is added to at least one of the constituent members to prevent defects in image display devices caused by charging.
[0004] On the other hand, as usage environments diversify, image display devices are required to have improved durability in high-temperature and high-humidity environments.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2022-013705 Summary of the invention
[0008] Problems to be solved by the invention
[0009] The inventors have studied the durability of image display devices under high temperature and high humidity environments, and found that under high temperature and high humidity, cracks may occur in the phase difference layer, and iodine contained in the polarizer may flow out into the image display panel, and antistatic agents may flow out into the image display panel, which may cause corrosion in the electrodes provided in the image display panel. In addition, it is also known that as the phase difference layer, a phase difference film composed of a stretched film of a resin film or a phase difference film composed of an oriented solidified layer of a liquid crystal compound is mainly used, and such a problem tends to occur in the following manner: it is easy to occur when a phase difference film composed of a stretched film of a resin film having better reflective properties is used, and it is not easy to occur when a phase difference film composed of an oriented solidified layer of a liquid crystal compound is used.
[0010] The present invention has been made based on the above findings, and a main object of the present invention is to provide a polarizing plate with a retardation layer that can contribute to improving the durability of an image display device under high temperature and high humidity.
[0011] Means for solving problems
[0012] According to an embodiment of the present invention, there are provided the following polarizing plates or image display devices with a retardation layer [1] to
[10] .
[0013] [1] A polarizing plate with a phase difference layer, comprising a first main surface and a second main surface facing each other, and comprising, in order from the first main surface toward the second main surface, a polarizing plate containing a polarizer, a first adhesive layer, a first phase difference layer, an adhesive layer, a second phase difference layer, and a second adhesive layer, wherein the polarizing plate with a phase difference layer comprises an adhesive layer containing an antistatic agent, the tensile elastic modulus of an adjacent layer of the first phase difference layer adjacent to the second main surface side at 110° C. is 1 MPa or more, the amount of the antistatic agent added in the adhesive layer containing the antistatic agent is 5 phr or less, and when the polarizing plate with a phase difference layer is bonded to a surface of an aluminum layer of a laminate comprising a polyethylene terephthalate resin film having a thickness of 50 μm and an aluminum layer having a thickness of 0.05 μm provided on one surface thereof via the second adhesive layer, the resistivity change of the aluminum layer after being kept at 110° C. and 85% RH for 36 hours is 2 or less.
[0014] [2] A polarizing plate with a phase difference layer according to [1], wherein the first phase difference layer is a stretched film of a resin film, Re(550) of the first phase difference layer is 100nm to 190nm, Re(450) / Re(550) is greater than 0.8 and less than 1, and the angle between the slow axis of the first phase difference layer and the absorption axis of the polarizer is 40° to 50°.
[0015] [3] The polarizing plate with a retardation layer according to [1] or [2], wherein the thickness of the first retardation layer is 10 μm or more.
[0016] [4] The polarizing plate with a retardation layer according to [2], wherein the second retardation layer exhibits a refractive index characteristic of nz>nx=ny.
[0017] [5] The polarizing plate with a retardation layer according to any one of [1] to [4], wherein the surface resistivity of the first adhesive layer and / or the second adhesive layer is 9×10 11 Ω / sq or less.
[0018] [6] The polarizing plate with a retardation layer according to any one of [1] to [5], wherein the antistatic agent comprises bistrifluoromethanesulfonimide (N(SO2CF3)2 - ) as an ionic compound.
[0019] [7] The polarizing plate with a retardation layer according to any one of [1] to [6], wherein the adjacent layer is the adhesive layer.
[0020] [8] The polarizing plate with a retardation layer according to any one of [1] to [6], wherein the adjacent layer is a hard coat layer formed directly on the second main surface side of the first retardation layer.
[0021] [9] An image display device comprising an image display panel and the polarizing plate with a retardation layer according to any one of [1] to [8] disposed on a viewing side of the image display panel.
[0022]
[10] The image display device according to [9], wherein the image display panel includes an electrode, and the resistivity of the electrode changes to less than 2 after being kept at 110° C. and 85% RH for 36 hours.
[0023] Effects of the Invention
[0024] According to an embodiment of the present invention, a high elastic layer is provided adjacent to the first phase difference layer, thereby suppressing the thermal shrinkage of the first phase difference layer and the generation of cracks caused by the thermal shrinkage, and the amount of the antistatic agent added is set to a range in which a sufficient antistatic function can be obtained in practical use without greatly plasticizing the adhesive layer. Thus, the outflow of iodine or the antistatic agent to the image display panel can be suppressed, and the adverse conditions caused by these can be prevented, and as a result, the durability of the image display device under high temperature and high humidity can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic cross-sectional view of a polarizing plate with a retardation layer in one embodiment of the present invention.
[0026] Figure 2 This is a schematic cross-sectional view of a polarizing plate with a retardation layer in one embodiment of the present invention.
[0027] Figure 3 This is a schematic diagram for explaining a usage mode of a polarizing plate with a retardation layer in one embodiment of the present invention. DETAILED DESCRIPTION
[0028] Hereinafter, the embodiments of the present invention will be described with reference to the accompanying drawings, but the present invention is not limited to these embodiments. In order to make the description clearer, the drawings sometimes schematically show the width, thickness, shape, etc. of each part compared with the embodiments, but this is an example and does not limit the interpretation of the present invention. In addition, in this specification, (meth)acrylic acid refers to acrylic acid and / or methacrylic acid.
[0029] (Definition of Terms and Symbols)
[0030] The definitions of terms and symbols in this specification are as follows.
[0031] (1) Refractive index (nx, ny, nz)
[0032] “nx” is the refractive index in the direction where the refractive index in the plane is maximum (ie, the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), and “nz” is the refractive index in the thickness direction.
[0033] (2) In-plane phase difference (Re)
[0034] "Re(λ)" is the in-plane phase difference measured by light of wavelength λnm at 23°C. For example, "Re(550)" is the in-plane phase difference measured by light of wavelength 550nm at 23°C. When the thickness of the layer (film) is set to d(nm), Re(λ) is calculated by the formula: Re(λ) = (nx-ny)×d.
[0035] (3) Retardation in the thickness direction (Rth)
[0036] "Rth(λ)" is the phase difference in the thickness direction measured by light of wavelength λnm at 23°C. For example, "Rth(550)" is the phase difference in the thickness direction measured by light of wavelength 550nm at 23°C. When the thickness of the layer (film) is set to d(nm), Rth(λ) is calculated by the formula: Rth(λ) = (nx-nz)×d.
[0037] (4) Nz coefficient
[0038] The Nz coefficient is obtained by Nz=Rth / Re.
[0039] (5) Angle
[0040] When an angle is mentioned in this specification, the angle includes both clockwise and counterclockwise relative to a reference direction. Therefore, for example, "45°" means 45° clockwise and 45° counterclockwise.
[0041] A. Polarizing plate with phase difference layer
[0042] The polarizer with a phase difference layer of the embodiment of the present invention has a first main surface and a second main surface opposite to each other, and from the first main surface toward the second main surface, it includes a polarizer containing a polarizer, a first adhesive layer, a first phase difference layer, an adhesive layer, a second phase difference layer and a second adhesive layer in sequence, and the tensile elastic modulus of the adjacent layer of the first phase difference layer adjacent to the second main surface side at 110°C is 1MPa or more, and the polarizer with a phase difference layer includes an adhesive layer containing an antistatic agent, and the amount of the antistatic agent added in the adhesive layer containing the antistatic agent is 5phr or less. It should be noted that in the present invention, the adjacent layer of the first phase difference layer adjacent to the second main surface side is a layer adjacent to the first phase difference layer in a manner of directly contacting the first phase difference layer.
[0043] The polarizer with a phase difference layer of the embodiment of the present invention is in a state where the aluminum layer surface of the laminate comprising a PET resin film with a thickness of 50 μm and an aluminum layer with a thickness of 0.05 μm disposed on one surface thereof is bonded via the second adhesive layer, and the resistivity change of the aluminum layer after being kept for 36 hours under 110°C 85% RH conditions (resistivity after keeping / resistivity before keeping) is representatively 2 or less, preferably 1.8 or less, more preferably 1.5 or less, and further preferably 1.2 or less. The resistivity change of the aluminum layer can be obtained by the method described in the examples.
[0044] A-1. Overall structure of polarizing plate with retardation layer
[0045] Figure 1 1 is a schematic cross-sectional view of a polarizer with a phase difference layer according to an embodiment of the present invention. The polarizer 100A with a phase difference layer has a first main surface 100a and a second main surface 100b, and includes a polarizer 10, a first adhesive layer 20, a first phase difference layer 30, an adhesive layer 40, a second phase difference layer 50, and a second adhesive layer 60 in sequence from the first main surface 100a to the second main surface 100b. The polarizer 10 has a polarizer 12, a first protective layer 14a disposed on the side opposite to the side where the first phase difference layer 30 is disposed of the polarizer 12, and a second protective layer 14b disposed on the side where the first phase difference layer 30 is disposed. The polarizer 10 and the first phase difference layer 30 are bonded via the first adhesive layer 20. In addition, the first phase difference layer 30 and the second phase difference layer 50 are bonded via the adhesive layer 40. In the present embodiment, the adjacent layer of the first retardation layer 30 adjacent to the second major surface 100 b side is the adhesive layer 40 .
[0046] Figure 21 is a schematic cross-sectional view of a polarizer with a phase difference layer according to an embodiment of the present invention. The polarizer with a phase difference layer 100B has a first main surface 100a and a second main surface 100b, and includes a polarizer 10, a first adhesive layer 20, a first phase difference layer 30, a hard coat layer 70, an adhesive layer 40, a second phase difference layer 50, and a second adhesive layer 60 in sequence from the first main surface 100a to the second main surface 100b. The polarizer 10 has a polarizer 12, a first protective layer 14a disposed on the side opposite to the side where the first phase difference layer 30 is disposed of the polarizer 12, and a second protective layer 14b disposed on the side where the first phase difference layer 30 is disposed. The polarizer 10 and the first phase difference layer 30 are bonded via the first adhesive layer 20. Furthermore, the hard coating layer 70 is directly formed on the second main surface 100b side surface of the first retardation layer 30, and the second retardation layer 50 is bonded to the second main surface side via the adhesive layer 40. In this embodiment, the adjacent layer of the first retardation layer 30 adjacent to the second main surface 100b side is the hard coating layer 70.
[0047] The polarizing plate with a phase difference layer of an embodiment of the present invention includes an adhesive layer containing an antistatic agent. Typically, at least one selected from the first adhesive layer and the second adhesive layer includes an antistatic agent. For example, in an organic EL display device assembled with a touch panel, when a finger touches the display portion, light emission is sometimes generated unintentionally. The light emission is mainly caused by the static electricity charged by contact. In addition, in a liquid crystal display device, poor orientation of liquid crystal compounds is sometimes induced by static electricity. In contrast, by using an adhesive layer containing an antistatic agent, such adverse effects on the image display device caused by static electricity can be prevented. In the case where the second adhesive layer present near the image display panel includes an antistatic agent, such adverse effects on the image display device caused by static electricity can be appropriately prevented. On the other hand, in the case where the first adhesive layer present far from the image display panel includes an antistatic agent, in addition to preventing such adverse effects, it is also advantageous in that corrosion of touch sensor electrodes such as an aluminum layer caused by an antistatic agent can be suppressed.
[0048] In the polarizing plate with a retardation layer according to the embodiment of the present invention, the surface resistivity of the second adhesive layer side surface is preferably 9.0×10 11 Ω / sq or less, more preferably 1.0×10 8 Ω / sq~8.0×10 11 Ω / sq, more preferably 5.0×10 8 Ω / sq~6.0×10 11 Ω / sq.
[0049] The structure of the polarizing plate with a phase difference layer according to the embodiment of the present invention is not limited to the example shown in the figure. Specifically, one of the first protective layer 14a and the second protective layer 14b, for example, the second protective layer 14b may be omitted depending on the purpose. In addition, a release liner (not shown) may be temporarily attached to the side surface of the second adhesive layer 60 of the polarizing plate 100A, 100B with a phase difference layer. The release liner can protect the second adhesive layer 60 until the polarizing plate 100A, 100B with a phase difference layer is provided for use. In actual use, if Figure 3 As shown in , the polarizing plate 100 with a phase difference layer is attached to the visible side of an image display panel 200 such as an organic EL panel or a liquid crystal panel via a second adhesive layer on the second main surface 100b side, thereby forming an image display device 300. The image display panel 200 typically includes electrodes (including a conductive layer of a laminated structure of an Al layer and a Ti layer, etc.) for driving or touch sensors of a display element on its surface and / or inside.
[0050] The polarizer with a phase difference layer can be in the form of a long strip or a single sheet. Here, the so-called "long strip" refers to an elongated shape with a length sufficiently long relative to the width, for example, an elongated shape with a length of more than 10 times, preferably more than 20 times the width. The long strip polarizer with a phase difference layer can be wound into a roll.
[0051] The thickness of the polarizing plate with a retardation layer excluding the second pressure-sensitive adhesive layer (the thickness from the polarizing plate to the second retardation layer) is, for example, 50 to 120 μm, preferably 70 to 100 μm, and more preferably 80 to 90 μm.
[0052] A-2. Polarizing plate
[0053] The polarizer 10 typically includes a polarizer and a protective layer disposed on one side or both sides thereof. Preferably, the polarizer 10 includes a polarizer 12 and a first protective layer 14a disposed on the side of the polarizer 12 opposite to the side on which the first phase difference layer 30 is disposed. The second protective layer 14b disposed on the side of the first phase difference layer 30 of the polarizer 12 can be omitted according to the purpose. In one embodiment, the polarizer and the protective layer are bonded via an adhesive layer (representatively an adhesive layer). For example, the polarizer and the protective layer are bonded using an active energy ray-curing adhesive. In other embodiments, the polarizer and the protective layer are laminated in close contact without an adhesive layer.
[0054] A-2-1. Polarizer
[0055] The polarizer is typically a resin film containing a dichroic substance (eg, iodine). Examples of the resin film include hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified ethylene / vinyl acetate copolymer films.
[0056] The thickness of the polarizer is preferably 18 μm or less, more preferably 15 μm or less, and further preferably 12 μm or less. On the other hand, the thickness of the polarizer is preferably 1 μm or more.
[0057] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is, for example, 41.5% to 46.0%, preferably 42.0% to 46.0%, and more preferably 44.5% to 46.0%. The polarization degree of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and further preferably 99.9% or more.
[0058] The polarizer can be produced by any appropriate method. Specifically, the polarizer can be produced using a single-layer resin film or a laminate of two or more layers.
[0059] The method of making a polarizer by the above-mentioned monolayer resin film typically includes dyeing and stretching the resin film using dichroic substances such as iodine or dichroic dyes. As the resin film, for example, hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially methylated PVA films, and partially saponified films of ethylene / vinyl acetate copolymers are used. The method may further include insolubilization treatment, swelling treatment, crosslinking treatment, etc. Such a manufacturing method is well known and commonly used in the art, so detailed description is omitted.
[0060] The polarizer obtained using the above-mentioned laminate can be made, for example, using a laminate of a resin substrate and a resin film or a resin layer (representatively a PVA-based resin layer). Specifically, it can be made in the following manner: a PVA-based resin solution is applied to a resin substrate and dried to form a PVA-based resin layer on the resin substrate to obtain a laminate of a resin substrate and a PVA-based resin layer; the laminate is stretched and dyed to make the PVA-based resin layer into a polarizer. In this embodiment, it is preferred that a PVA-based resin layer containing a halide and a PVA-based resin is formed on one side of the resin substrate. Stretching typically includes immersing the laminate in a boric acid aqueous solution for stretching. Furthermore, stretching may further include stretching the laminate at a high temperature (e.g., above 95°C) in the air before stretching in a boric acid aqueous solution as required. In addition, in this embodiment, it is preferred that the laminate is provided with a drying shrinkage treatment that shrinks by more than 2% in the width direction by heating while conveying in the length direction. Typically, the manufacturing method of this embodiment includes sequentially performing an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment on the laminate. By introducing auxiliary stretching, even when PVA is coated on a thermoplastic resin, the crystallinity of PVA can be improved, and high optical properties can be achieved. In addition, by improving the orientation of PVA in advance, when immersed in water in the subsequent dyeing process and stretching process, the problems of reduction and dissolution of the orientation of PVA can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of the PVA molecules and the reduction of the orientation can be suppressed compared to the case where the PVA-based resin layer does not contain a halide, and high optical properties can be achieved. Furthermore, by utilizing a drying shrinkage treatment to shrink the laminate in the width direction, high optical properties can be achieved. A polarizer can be obtained by laminating a protective layer on the peeling surface obtained by peeling the resin substrate from the obtained resin substrate / polarizer laminate, or on the surface opposite to the peeling surface. The details of the manufacturing method of such a polarizer are recorded in, for example, Japanese Patent Publication No. 2012-73580 and Japanese Patent No. 6470455. The entire contents of these publications are incorporated herein by reference.
[0061] A-2-2. First protective layer
[0062] The first protective layer can be formed by any suitable resin film that can be used as a protective layer of a polarizer. Specific examples of the resin that is the main component of the resin film include cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyether sulfone resins, polysulfone resins, polystyrene resins, cycloolefin resins such as polynorbornene, polyolefin resins, (meth) acrylic resins, acetate resins, etc.
[0063] The polarizer with a phase difference layer is typically arranged on the visible side of an image display device (e.g., an organic EL display device), and the first protective layer is arranged on the visible side. Therefore, the first protective layer may also be subjected to surface treatments such as hard coating (HC), anti-reflection, anti-adhesion, and anti-glare as required.
[0064] The thickness of the first protective layer is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and further preferably 15 μm to 35 μm. When the surface treatment is performed, the thickness of the first protective layer includes the thickness of the surface treatment layer.
[0065] A-2-3. Second protective layer
[0066] The second protective layer can be formed by any suitable resin film that can be used as the protective layer of the polarizer. For the second protective layer formed by the resin film, the same description as the first protective layer can be applied. In addition, for example, the second protective layer can be a solidified layer or a hardened layer of a coating film of an organic solvent solution containing a resin. By having the second protective layer be a solidified layer or a hardened layer of a coating film of an organic solvent solution containing a resin, the adhesion to the polarizer can be improved.
[0067] In one embodiment, the glass transition temperature (Tg) of the resin (base polymer) forming the solidified layer or the hardened layer may be 85°C or more, and the weight average molecular weight Mw may be 25,000 or more. By having the Tg and Mw of the resin in such a range, excellent durability in a high temperature and high humidity environment can be achieved despite a very thin thickness. The Tg of the resin is preferably 90°C or more, more preferably 100°C or more, further preferably 110°C or more, and particularly preferably 120°C or more. Tg may be, for example, 200°C or less. In addition, the Mw of the resin is preferably 30,000 or more, more preferably 35,000 or more, and further preferably 40,000 or more. Mw may be, for example, 150,000 or less.
[0068] As the resin, any suitable resin can be used as long as it is a solidified material or a hardened material (e.g., a thermosetting material) that can form a coating film of an organic solvent solution. Preferably, it is a thermoplastic resin or a thermosetting resin having Tg and Mw as described above, and more preferably a thermoplastic resin. Only one type of resin may be used, or two or more types may be used in combination.
[0069] Examples of the thermoplastic resin include acrylic resins and epoxy resins. An acrylic resin and an epoxy resin may be used in combination.
[0070] Acrylic resins typically contain repeating units derived from (meth)acrylate monomers having a linear or branched structure as the main component. Acrylic resins may contain repeating units derived from any suitable comonomer corresponding to the purpose. As comonomers (comonomers), for example, carboxyl-containing monomers, hydroxyl-containing monomers, amide-containing monomers, aromatic ring-containing (meth)acrylates, and heterocyclic vinyl monomers can be listed. By appropriately setting the type, number, combination, and copolymerization ratio of the monomer units, an acrylic resin having the Tg and Mw specified above can be obtained. As specific examples of acrylic resins, boron-containing acrylic resins and acrylic resins containing lactone rings, etc., described in
[0034] to
[0056] of Japanese Patent Publication No. 2021-117484, can be listed.
[0071] As the epoxy resin, an epoxy resin having an aromatic ring is preferably used. By using an epoxy resin having an aromatic ring as the epoxy resin, the adhesion between the protective layer and the polarizer can be improved. Furthermore, when an adhesive layer is arranged adjacent to the protective layer, the anchoring force of the adhesive layer can be improved. As the epoxy resin having an aromatic ring, for example, bisphenol-type epoxy resins such as bisphenol A epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin; phenol novolac epoxy resins such as phenol novolac epoxy resin, cresol novolac epoxy resin, and hydroxybenzaldehyde phenol novolac epoxy resin; polyfunctional epoxy resins such as glycidyl ether of tetrahydroxyphenylmethane, glycidyl ether of tetrahydroxybenzophenone, and epoxidized polyvinylphenol, naphthol epoxy resin, naphthalene epoxy resin, biphenyl epoxy resin, etc. Bisphenol A epoxy resin, biphenyl epoxy resin, and bisphenol F epoxy resin are preferably used. The epoxy resin may be used alone or in combination of two or more.
[0072] The second protective layer can be formed by applying an organic solvent solution of the above-mentioned resin to form a coating film and curing or heat-hardening the coating film. As an organic solvent, any suitable organic solvent that can dissolve or uniformly disperse acrylic resin or epoxy resin can be used. As specific examples of organic solvents, ethyl acetate, toluene, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclopentanone, and cyclohexanone can be listed. The resin concentration of the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. If it is such a resin concentration, a uniform coating film can be formed.
[0073] The solution can be applied to any suitable substrate or to a polarizer. When the solution is applied to the substrate, the solidified or hardened product (resin layer) of the coating film formed on the substrate can be transferred to the polarizer. When the solution is applied to the polarizer, a protective layer is directly formed on the polarizer by drying (curing) or hardening the coating film. Preferably, the solution is applied to the polarizer to form a protective layer directly on the polarizer. If it is such a structure, the adhesive layer or adhesive layer required for transfer can be omitted, so the polarizer can be further thinned. As a coating method for the solution, any suitable method can be adopted. As specific examples, roller coating, spin coating, wire rod coating, dip coating, die coating, curtain coating, spray coating, and blade coating (comma coating, etc.) can be listed.
[0074] The protective layer can be formed by curing or thermally curing the coating film of the solution. The heating temperature for curing or thermally curing is preferably below 100° C., more preferably 50° C. to 70° C. If the heating temperature is in such a range, it is possible to prevent adverse effects on the polarizer. The heating time can vary depending on the heating temperature. The heating time can be, for example, 1 minute to 10 minutes.
[0075] The second protective layer (substantially an organic solvent solution of the above-mentioned resin) may also contain any suitable additives according to the purpose. Specific examples of additives include ultraviolet absorbers; leveling agents; antioxidants such as hindered phenols, phosphorus, and sulfur; stabilizers such as light stabilizers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fibers and carbon fibers; near-infrared absorbers; flame retardants such as tris(dibromopropyl) phosphate, triallyl phosphate, and antimony oxide; antistatic agents such as anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic fillers or inorganic fillers; resin modifiers; organic fillers and inorganic fillers; plasticizers; lubricants; flame retardants, etc. The type, number, combination, and addition amount of additives can be appropriately set according to the purpose.
[0076] The thickness of the second protective layer in the case of a solidified layer or cured layer of a coating film composed of an organic solvent solution of a resin is preferably 0.05 to 10 μm, more preferably 0.08 to 5 μm, further preferably 0.1 to 1 μm, particularly preferably 0.2 to 0.7 μm.
[0077] A-3. First phase difference layer
[0078] The first phase difference layer 30 may have any suitable optical and / or mechanical properties depending on the purpose. The first phase difference layer typically has a slow axis. In one embodiment, the angle θ between the slow axis of the first phase difference layer 30 and the absorption axis of the polarizer 12 is, for example, 40° to 50°, preferably 42° to 48°, and more preferably about 45°. If the angle θ is in such a range, by setting the first phase difference layer to a λ / 4 plate, a polarizing plate with a phase difference layer having very excellent circular polarization properties (as a result, very excellent anti-reflection properties) can be obtained.
[0079] The refractive index characteristics of the first phase difference layer preferably show the relationship of nx>ny≥nz. In one embodiment, the first phase difference layer can function as a λ / 4 plate. In this case, the in-plane phase difference Re(550) of the first phase difference layer is, for example, 100nm to 190nm, preferably 110nm to 170nm, and more preferably 130nm to 160nm. It should be noted that "ny=nz" here includes not only the case where ny and nz are completely equal, but also the case where they are substantially equal. Therefore, within the range that does not impair the effect of the present invention, ny may sometimes be <nz。
[0080] The Nz coefficient of the first retardation layer is preferably 0.9 to 3, more preferably 0.9 to 2.5, further preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3. When such a relationship is satisfied, when the obtained polarizing plate with a retardation layer is used in an image display device, a very excellent reflection hue can be achieved.
[0081] The first phase difference layer can show a reverse dispersion wavelength characteristic in which the phase difference value increases correspondingly with the wavelength of the measurement light, or a positive wavelength dispersion characteristic in which the phase difference value decreases correspondingly with the wavelength of the measurement light, or a flat wavelength dispersion characteristic in which the phase difference value does not change substantially according to the wavelength of the measurement light. In one embodiment, the first phase difference layer shows a reverse dispersion wavelength characteristic. In this case, Re(450) / Re(550) of the phase difference layer is, for example, greater than 0.8 and less than 1, preferably greater than 0.8 and less than 0.95. If it is such a structure, a very excellent anti-reflection property can be achieved.
[0082] The absolute value of the photoelastic modulus of the first retardation layer is preferably 2×10 -11 m 2 / N or less, more preferably 2.0×10 -13 m 2 / N~1.5×10 -11 m 2 / N, more preferably 1.0×10 -12 m 2 / N~1.2×10-11 m 2 / N resin. If the absolute value of the photoelastic modulus is within such a range, the phase difference is unlikely to change when shrinkage stress is generated during heating. As a result, thermal unevenness of the obtained image display device can be well prevented.
[0083] The first phase difference layer is typically composed of a stretched film of a resin film. The thickness of the first phase difference layer is, for example, 10 μm or more, preferably 10 μm to 70 μm, more preferably 10 μm to 50 μm, and further preferably 20 μm to 40 μm. If the thickness of the first phase difference layer is within such a range, curling during heating can be well suppressed and curling during lamination can be well adjusted.
[0084] The first phase difference layer is composed of any suitable resin film that can satisfy the above-mentioned characteristics. As a representative example of such a resin, polycarbonate resins, polyester carbonate resins, polyester resins, polyvinyl acetal resins, polyarylate resins, cyclic olefin resins, cellulose resins, polyvinyl alcohol resins, polyamide resins, polyimide resins, polyether resins, polystyrene resins, and acrylic resins can be listed. These resins can be used alone or in combination (for example, blended, copolymerized). In the case where the first phase difference layer is composed of a resin film showing reverse dispersion wavelength characteristics, polycarbonate resins or polyester carbonate resins (hereinafter, sometimes referred to as polycarbonate resins) can be appropriately used.
[0085] As the above-mentioned polycarbonate resin, any suitable polycarbonate resin can be used as long as the effect of the present invention can be obtained. For example, the polycarbonate resin contains a structural unit derived from a fluorene dihydroxy compound, a structural unit derived from an isosorbide dihydroxy compound, and a structural unit derived from at least one dihydroxy compound selected from the group consisting of alicyclic diols, alicyclic dimethanol, diethylene glycol, triethylene glycol or polyethylene glycol, and an alkylene glycol or spiro glycol. Preferably, the polycarbonate resin contains a structural unit derived from a fluorene dihydroxy compound, a structural unit derived from an isosorbide dihydroxy compound, and a structural unit derived from alicyclic dimethanol and / or a structural unit derived from diethylene glycol, triethylene glycol or polyethylene glycol; more preferably, it contains a structural unit derived from a fluorene dihydroxy compound, a structural unit derived from an isosorbide dihydroxy compound, and a structural unit derived from diethylene glycol, triethylene glycol or polyethylene glycol. The polycarbonate resin may also contain structural units derived from other dihydroxy compounds as needed. It should be noted that the details of the polycarbonate resin that can be suitably used for the first phase difference layer and the method for forming the first phase difference layer are described in, for example, Japanese Patent Publication No. 2014-10291, Japanese Patent Publication No. 2014-26266, Japanese Patent Publication No. 2015-212816, Japanese Patent Publication No. 2015-212817, and Japanese Patent Publication No. 2015-212818, and the descriptions of these publications are cited in this specification as a reference.
[0086] The first phase difference layer may also contain any suitable additives according to the purpose. Specific examples of additives include ultraviolet absorbers; leveling agents; antioxidants; stabilizers such as light stabilizers, weather stabilizers, and heat stabilizers. In one embodiment, the first phase difference layer contains an ultraviolet absorber. The ultraviolet absorption capacity usually increases in proportion to the thickness of the material. Therefore, by adding an ultraviolet absorber to the first phase difference layer composed of a resin film and having a specified thickness, the added concentration can be reduced. As a result, excessive addition can be avoided, so compatibility can be ensured and precipitation problems can be prevented. The type, number, combination, and amount of additives can be appropriately set according to the purpose.
[0087] In one embodiment, by making the second main surface side surface of the first phase difference layer contact an organic solvent, then, an adhesive layer is provided on the contact surface, and a compatible region whose composition changes continuously from the first phase difference layer side toward the adhesive layer side can be formed on the second main surface side of the first phase difference layer. By forming a compatible region in which the constituent components of the first phase difference layer are compatible with the constituent components of the adhesive layer, the adhesion of the first phase difference layer to the second phase difference layer can be improved. On the other hand, from the viewpoint of strictly suppressing the infiltration of moisture into the first phase difference layer (as a result, the swelling of the first phase difference layer), it is preferred that a compatible region is not provided. Therefore, the compatible region is preferably formed as needed considering the adhesion between the first phase difference layer and the second phase difference layer, the purpose or use environment of the polarizer with a phase difference layer, etc. The details of the method for forming a compatible region are described in Japanese Patent Publication No. 2019-56820, which is cited in this specification as a reference.
[0088] A-4. Second phase difference layer
[0089] The second retardation layer 50 may be a so-called positive C plate whose refractive index characteristic shows the relationship of nz>nx=ny. By using a positive C plate as the second retardation layer, reflection in an oblique direction can be well prevented, and the anti-reflection function can be extended to a wider viewing angle.
[0090] The thickness direction phase difference Rth(550) of the second phase difference layer is preferably -50nm to -300nm, more preferably -70nm to -250nm, further preferably -90nm to -200nm, and particularly preferably -100nm to -180nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane phase difference Re(550) of the second phase difference layer can be less than 10nm.
[0091] The second phase difference layer having a refractive index characteristic of nz>nx=ny can be formed by any suitable material. The second phase difference layer preferably includes a film containing a liquid crystal material fixed in a vertical orientation. The vertically oriented liquid crystal material (liquid crystal compound) can be a liquid crystal monomer or a liquid crystal polymer. As specific examples of the liquid crystal compound and the method for forming the phase difference layer, the liquid crystal compound and the method for forming the phase difference layer described in
[0020] to
[0028] of Japanese Patent Gazette No. 2002-333642 can be listed. In this case, the thickness of the second phase difference layer is preferably 0.5μm to 10μm, more preferably 0.5μm to 8μm, and further preferably 0.5μm to 5μm.
[0092] A-5. Adhesive layer
[0093] The storage elastic modulus of the first adhesive layer 20 and the second adhesive layer 60 (hereinafter, the first adhesive layer and the second adhesive layer are sometimes collectively referred to as adhesive layers) at 110°C is preferably 0.01 MPa or more, more preferably 0.01 MPa to 1 MPa, and more preferably 0.02 MPa to 0.5 MPa. In addition, the storage elastic modulus of the first adhesive layer 20 and the second adhesive layer 60 at 23°C is preferably 0.05 MPa or more, more preferably 0.05 MPa to 1 MPa, and more preferably 0.07 MPa to 0.5 MPa. By using an adhesive layer having such a storage elastic modulus, it is possible to suppress thermal shrinkage of the first phase difference layer under high temperature and high humidity, and as a result, the effect of the present invention can be more suitably obtained.
[0094] The adhesive constituting the adhesive layer typically contains a (meth) acrylic polymer, a urethane polymer, a silicone polymer or a rubber polymer as a base polymer, preferably a (meth) acrylic polymer. When a (meth) acrylic polymer is used as the base polymer, the adhesive layer is formed, for example, from an adhesive containing a (meth) acrylic polymer.
[0095] A-5-1. (Meth)acrylic acid polymer
[0096] The (meth)acrylic acid polymer preferably has a constituent unit derived from an alkyl (meth)acrylate having an alkyl group having 1 to 30 carbon atoms in the side chain. The alkyl group may be linear or branched. Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate (lauryl (meth)acrylate), n-tridecyl (meth)acrylate, and n-tetradecyl (meth)acrylate. In addition, alkyl (meth)acrylates having a long-chain alkyl group (eg, an alkyl group having 6 to 30 carbon atoms) in a side chain, such as n-dodecyl (meth)acrylate (lauryl (meth)acrylate), may be used. One or more alkyl (meth)acrylates may be used.
[0097] The content of the alkyl (meth)acrylate in all monomers constituting the (meth)acrylic polymer is, for example, 50% by weight or more, preferably 60% by weight or more, more preferably 70% by weight or more, and even more preferably 80% by weight or more. The upper limit of the content may be, for example, 99.9% by weight or less.
[0098] The (meth)acrylic acid polymer may also have a constituent unit other than the constituent unit derived from the (meth)acrylic acid alkyl ester. The constituent unit is derived from a monomer (comonomer) copolymerizable with the (meth)acrylic acid alkyl ester. The (meth)acrylic acid polymer may also have one or more constituent units derived from the comonomer.
[0099] As examples of copolymerizable monomers, aromatic ring-containing monomers can be cited. Aromatic ring-containing monomers can also be (meth) acrylic monomers containing aromatic rings. Specific examples of aromatic ring-containing monomers include phenyl (meth) acrylate, phenoxyethyl (meth) acrylate, benzyl (meth) acrylate, phenoxydiethylene glycol (meth) acrylate, ethylene oxide-modified nonylphenol (meth) acrylate, hydroxyethylated β-naphthol (meth) acrylate, and biphenyl (meth) acrylate. The proportion of aromatic ring-containing monomers in all monomers constituting the (meth) acrylic polymer is, for example, 0% to 50% by weight, or 1% to 30% by weight, 5% to 25% by weight, or 8% to 20% by weight.
[0100] Other examples of the comonomer include (meth)acrylates represented by the following chemical formula (1). 1 is an alkyl group. The alkyl group may be linear or branched. 1 Preferably, it is a straight-chain alkyl group. 1 Examples of are methyl and ethyl. n in formula (1) is an integer of 1-15.
[0101] [Chemical formula 1]
[0102]
[0103] Specific examples of the (meth)acrylate shown in formula (1) include 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate and methoxytriethylene glycol (meth)acrylate. By using the (meth)acrylate of formula (1), when an antistatic agent is added to the adhesive layer, an adhesive layer with a low surface resistivity can be achieved with a small amount of addition. The content ratio of the (meth)acrylate of formula (1) in all monomers constituting the (meth)acrylic polymer is, for example, 5% to 95% by weight, and can be 10% to 90% by weight, 20% to 80% by weight, or 25% to 75% by weight.
[0104] The comonomer may also be a polar group-containing monomer selected from carboxyl-containing monomers, amino-containing monomers, hydroxyl-containing monomers and amide-containing monomers. If a base polymer having a polar group is used, the outflow of the antistatic agent can be more suitably suppressed in the case of an antistatic agent. As specific examples of carboxyl-containing monomers, (meth) acrylic acid, (meth) carboxyethyl acrylate, (meth) carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid and crotonic acid can be listed. As specific examples of amino-containing monomers, N, N-dimethylaminoethyl (meth) acrylate and N, N-dimethylaminopropyl (meth) acrylate can be listed. Specific examples of the hydroxyl group-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)-methacrylate. Specific examples of the amide group-containing monomer include acrylamide monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropylacrylamide, N-methyl(meth)acrylamide, N-butyl(meth)acrylamide, N-hexyl(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-hydroxymethyl-N-propane(meth)acrylamide, aminomethyl(meth)acrylamide, aminoethyl(meth)acrylamide, mercaptomethyl(meth)acrylamide, and mercaptoethyl(meth)acrylamide; N-acryloyl heterocyclic monomers such as N-(meth)acryloylmorpholine, N-(meth)acryloylpiperidine, and N-(meth)acryloylpyrrolidine; and N-vinyl-containing lactam monomers such as N-vinylpyrrolidone and N-vinyl-ε-caprolactam.
[0105] The total content ratio of the above-mentioned polar group-containing monomers in all monomers constituting the (meth)acrylic polymer is, for example, 15% by weight or less, preferably 0.1% by weight to 10% by weight, and more preferably 0.1% by weight to 5% by weight. When the (meth)acrylic polymer is used in combination with an antistatic agent, the total content ratio of the above-mentioned polar group-containing monomers in all monomers constituting the (meth)acrylic polymer is, for example, 0.1% by weight or more, preferably 0.5% by weight to 10% by weight, and more preferably 0.5% by weight to 8% by weight.
[0106] The comonomer may also be a multifunctional monomer. As the multifunctional monomer, hexanediol di(meth)acrylate (1,6-hexanediol di(meth)acrylate), butanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, epoxy acrylate, polyester acrylate, and urethane acrylate and other multifunctional acrylates; and divinylbenzene. Preferred examples of the multifunctional acrylate include 1,6-hexanediol diacrylate and dipentaerythritol hexa(meth)acrylate.
[0107] The content of the multifunctional monomer in all monomers constituting the (meth)acrylic polymer is preferably 1% by weight or less, more preferably 0.9% by weight or less, and further preferably 0.8% by weight or less. The lower limit of the total content is, for example, 0.01% by weight or more, and may be 0.015% by weight or more, or 0.02% by weight or more. The (meth)acrylic polymer may not contain a constituent unit derived from a multifunctional monomer.
[0108] Other copolymerizable monomers include epoxy group-containing monomers such as glycidyl (meth)acrylate and methyl glycidyl (meth)acrylate; sulfonic acid group-containing monomers such as sodium vinyl sulfonate; phosphoric acid group-containing monomers; (meth)acrylates having alicyclic hydrocarbon groups such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate and isobornyl (meth)acrylate; vinyl esters such as vinyl acetate and vinyl propionate; aromatic vinyl compounds such as styrene and vinyl toluene; olefins such as ethylene, propylene, butadiene, isoprene and isobutylene, or dienes; vinyl ethers such as vinyl alkyl ether; and vinyl chloride.
[0109] The total content ratio of the above other copolymerizable monomers in all monomers constituting the (meth)acrylic polymer is, for example, 30% by weight or less, preferably 10% by weight or less, and may be 0% by weight.
[0110] (Meth) acrylic polymers can be formed by polymerizing one or more of the above-mentioned monomers by a known method. Monomers can also be polymerized with partial polymers (oligomers) of monomers. By using monomers with high glass transition temperature (Tg) (e.g., methyl (meth) acrylate, phenoxyethyl acrylate, benzyl acrylate, etc.) and / or oligomers with high Tg, and combining the obtained (meth) acrylic polymer with additives with high Tg (e.g., crosslinking agents), a highly elastic adhesive layer can be obtained. Polymerization can be implemented, for example, by solution polymerization, emulsion polymerization, bulk polymerization, thermal polymerization, active energy ray polymerization (e.g., UV polymerization). From the viewpoint of being able to form an adhesive layer with excellent optical transparency, solution polymerization or active energy ray polymerization is preferred.
[0111] The weight average molecular weight (Mw) of the (meth)acrylic polymer is, for example, 1,000,000 to 2,800,000, and is preferably 1,200,000 or more, and more preferably 1,400,000 or more, from the viewpoint of durability and heat resistance of the adhesive layer. The weight average molecular weight (Mw) is determined as a value (in terms of polystyrene) measured by GPC (gel permeation chromatography).
[0112] The content of the (meth)acrylic acid polymer in the adhesive is, for example, 50% by weight or more, preferably 60% by weight or more, more preferably 70% by weight or more, and further preferably 80% by weight or more, in terms of solid content ratio. The upper limit of the content ratio may be, for example, 99.9% by weight or less, preferably 99.8% by weight or less.
[0113] A-5-2. Antistatic agent
[0114] As described above, at least one of the first adhesive layer and the second adhesive layer contains an antistatic agent. The surface resistivity of the adhesive layer containing the antistatic agent is preferably 9.0×10 11 Ω / sq or less, more preferably 1.0×10 8 Ω / sq~8.0×10 11 Ω / sq, more preferably 5.0×10 8 Ω / sq~6.0×10 11 Ω / sq.
[0115] Examples of the antistatic agent include ionic compounds such as salts, and conductive polymers. The antistatic agent may be used alone or in combination of two or more.
[0116] Examples of the ionic compound include ionic liquids that are liquid at room temperature (25° C.) When the ionic compound is incorporated into the pressure-sensitive adhesive layer, it has high compatibility with the base polymer (typically a (meth)acrylic polymer) and can maintain optical transparency.
[0117] Examples of cations constituting ionic compounds include metal ions and onium ions. Examples of metal ions include alkali metal ions and alkaline earth metal ions. Examples of alkali metal ions include lithium ions, sodium ions, and potassium ions, and lithium ions may also be used. Examples of alkaline earth metal ions include magnesium ions and calcium ions.
[0118] Examples of onium ions include ions in which at least one atom selected from nitrogen, phosphorus and sulfur atoms has a positive (+) charge. Onium ions may be organic ions, in which case they may be ions of cyclic organic compounds or ions of chain organic compounds. Cyclic organic compounds may be aromatic or non-aromatic such as aliphatic. Specific examples of onium ions include N-ethyl-N,N-dimethyl-N-(2-methoxyethyl)ammonium ion, N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium ion, N-ethyl-N,N-dimethyl-N-propylammonium ion, N-methyl-N,N,N-trioctylammonium ion, N,N,N-trimethyl-N-propylammonium ion, tetrabutylammonium ion, tetramethylammonium ion, tetrahexylammonium ion and N-methyl-N,N,N-tributylammonium ion. Quaternary ammonium ions; pyridinium ions such as N-alkylpyridinium substituted with an alkyl group having 4 to 16 carbon atoms; imidazolium ions such as 1,3-alkylmethylimidazolium substituted with an alkyl group having 2 to 10 carbon atoms (e.g., ethyl) and 1,2-dimethyl-3-alkylimidazolium substituted with an alkyl group having 2 to 10 carbon atoms; phosphonium ions, pyrrolidinium ions, pyridazinium ions, pyrimidinium ions, pyrazinium ions, pyrazolium ions, thiazolium ions, oxazolium ions, triazolium ions, and piperidinium ions.
[0119] Specific examples of anions constituting ionic compounds include fluoride, chloride, bromide, iodide, perchlorate (ClO4 - ), hydroxide (OH - ), carbonate (CO3 2- ), nitrate (NO3 - ), sulfonate (SO4 - ), methylbenzenesulfonate (CH3(C6H4)SO3 - ), p-toluenesulfonate (CH3C6H4SO3 - ), carboxybenzenesulfonate (COOH(C6H4)SO3 - ), trifluoromethanesulfonate (CF3SO2 - ), benzoate (C6H5COO - ), acetate (CH3COO - ), trifluoroacetate (CF3COO - ), tetrafluoroborate (BF4 -), tetrabenzyl borate (B(C6H5)4 - ), hexafluorophosphate (PF6 - ), tris(pentafluoroethyl) trifluorophosphate (P(C2F5)3F3 - ), bis(fluorosulfonyl)imide (N(SO2F)2 - ), bis(trifluoromethanesulfonyl)imide(N(SO2CF3)2 - ), bis(pentafluoroethanesulfonyl)imide (N(SOC2F5)2 - ), bis(pentafluoroethanecarbonyl)imide (N(COC2F5)2 - ), bis(perfluorobutanesulfonyl)imide (N(SO2C4F9)2 - ), bis(perfluorobutanecarbonyl)imide (N(COC4F9)2 - ), tris(trifluoromethanesulfonyl) methylate (C(SO2CF3)3 - ) and tris(trifluoromethanecarbonyl)methyl (C(SO2CF3)3 - ).
[0120] The ionic compound may also contain anions containing sulfur atoms. Specific examples of anions containing sulfur atoms include bis(fluorosulfonyl)imide (N(SO2F)2 - ) and bis(trifluoromethanesulfonyl)imide (N(SO2CF3)2 - ).
[0121] The ionic compound may be an organic salt. In addition, the ionic compound may be a lithium salt, or a lithium organic salt containing a lithium ion and an organic ion as a cation and an anion, respectively.
[0122] Specific examples of the ionic compound are 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide (LiTFSi), ethylmethylpyrrolidinium bis(trifluoromethanesulfonyl)imide (EMP-TFSi), and tributylmethylammonium bis(trifluoromethanesulfonyl)imide (TBMA-TFSi).
[0123] The ionic compound does not need to contain phosphorus atoms. An ionic compound containing phosphorus atoms tends to easily corrode the touch panel (more specifically, the conductive layer of the touch panel).
[0124] Examples of the conductive polymer include polythiophene, polyaniline, polypyrrole, polyquinoxaline, polyacetylene, polyphenylenevinylene, polynaphthalene, and derivatives thereof. The conductive polymer is preferably polythiophene, polyaniline, and derivatives thereof, and more preferably a polythiophene derivative.
[0125] The conductive polymer may have a hydrophilic functional group. Examples of the hydrophilic functional group include sulfone group, amino group, amide group, imino group, hydroxyl group, mercapto group, hydrazine group, carboxyl group, sulfate group, phosphate group, and salts thereof (eg, quaternary ammonium salt group).
[0126] From the viewpoint of conductivity and chemical stability, the conductive polymer is preferably poly(3,4-disubstituted thiophene). Examples of the poly(3,4-disubstituted thiophene) include poly(3,4-alkylenedioxythiophene) and poly(3,4-dialkoxythiophene), and poly(3,4-alkylenedioxythiophene) is preferred. The poly(3,4-alkylenedioxythiophene) has a structural unit represented by the following formula (2), for example.
[0127] [Chemical formula 2]
[0128]
[0129] R in formula (2) 2 For example, it is an alkylene group having 1 to 4 carbon atoms. The alkylene group may be linear or branched. Examples of the alkylene group include methylene, 1,2-ethylene, 1,3-propylene, 1,4-butylene, 1-methyl-1,2-ethylene, 1-ethyl-1,2-ethylene, 1-methyl-1,3-propylene, and 2-methyl-1,3-propylene, preferably methylene, 1,2-ethylene, and 1,3-propylene, and more preferably 1,2-ethylene. The conductive polymer may also be poly(3,4-ethylenedioxythiophene) (PEDOT).
[0130] As a dopant, a polyanion can be used. When the conductive polymer is polythiophene (or its derivatives), the polyanion can form an ion pair with the polythiophene (or its derivatives). The polyanion is not particularly limited, and examples thereof include carboxylic acid polymers such as polyacrylic acid, polymaleic acid, and polymethacrylic acid; sulfonic acid polymers such as polystyrene sulfonic acid, polyvinyl sulfonic acid, and polyisoprene sulfonic acid. The polyanion can also be a copolymer of vinyl carboxylic acids or vinyl sulfonic acids with other monomers. As other monomers, (meth)acrylate compounds; aromatic vinyl compounds such as styrene and vinylnaphthalene can be listed. The polyanion is preferably polystyrene sulfonic acid (PSS). The conductive polymer as a complex with a dopant can be, for example, a complex of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid (PEDOT / PSS).
[0131] The amount of the antistatic agent in the adhesive layer is typically less than 5 phr (per hundred resin). Specifically, the amount of the antistatic agent in the adhesive layer is representatively less than 5 parts by weight, preferably 0.05 to 4 parts by weight, and more preferably 0.1 to 3 parts by weight, relative to 100 parts by weight of the base polymer. If the amount of the antistatic agent exceeds 5 phr, it is possible that the antistatic agent flows out into the image display panel and causes adverse effects. In addition, it is possible that the adhesive layer can be plasticized, and the effect of suppressing the thermal shrinkage of the first phase difference layer or the swelling caused by water absorption is reduced. In one embodiment, the amount of the antistatic agent containing phosphorus atoms in the adhesive layer is preferably less than 2.5 parts by weight, more preferably less than 2 parts by weight, and further preferably less than 1.5 parts by weight, for example, it can be 0 parts by weight.
[0132] A-5-3. Additives
[0133] The adhesive may further contain additives other than the antistatic agent. As specific examples of additives, powders such as silane coupling agents, crosslinking agents, antioxidants, colorants, pigments, dyes, surfactants, plasticizers, adhesiveness imparting agents, surface lubricants, leveling agents, softeners, anti-aging agents, light stabilizers, ultraviolet light absorbers, inhibitors, inorganic or organic fillers, metal powders, particles, foils may be listed. In addition, a redox system with a reducing agent may be used within a controllable range. The type, number, combination, content, etc. of the additive may be set to any suitable value according to the purpose.
[0134] As the crosslinking agent, an organic crosslinking agent and a multifunctional metal chelating agent can be listed. Examples of organic crosslinking agents are isocyanate crosslinking agents, peroxide crosslinking agents, epoxy crosslinking agents and imine crosslinking agents. The crosslinking agent is preferably a peroxide crosslinking agent and an isocyanate crosslinking agent. Only one crosslinking agent can be used, or two or more can be used in combination. For example, a peroxide crosslinking agent and an isocyanate crosslinking agent can be used in combination.
[0135] The amount of the crosslinking agent in the pressure-sensitive adhesive is, for example, 0.01 to 10 parts by weight, preferably 0.1 to 5 parts by weight, and more preferably 0.1 to 3 parts by weight, based on 100 parts by weight of the (meth)acryl-based polymer.
[0136] As the silane coupling agent, representative examples include functional group-containing silane coupling agents. As the functional group, for example, an epoxy group, a mercapto group, an amino group, an isocyanate group, an isocyanurate group, a vinyl group, a styryl group, an acetoacetyl group, a urea group, a thiourea group, a (meth) acrylic group, a heterocyclic group, an acid anhydride group, and combinations thereof can be listed. The silane coupling agent can be used alone or in combination of two or more.
[0137] The amount of the silane coupling agent in the adhesive is, for example, 0.01 to 5 parts by weight, preferably 0.01 to 3 parts by weight, and more preferably 0.01 to 1 part by weight, based on 100 parts by weight of the (meth)acrylic polymer.
[0138] The thickness of the first pressure-sensitive adhesive layer is typically 1 μm to 25 μm, preferably 2 μm to 20 μm, and more preferably 3 μm to 18 μm.
[0139] The thickness of the second pressure-sensitive adhesive layer is typically 5 μm to 50 μm, preferably 7 μm to 40 μm, and more preferably 10 μm to 30 μm.
[0140] A-6. Adhesive layer
[0141] As the adhesive constituting the adhesive layer 40, any suitable adhesive can be used. As the adhesive, representatively, an active energy ray-curing adhesive can be cited. As the active energy ray-curing adhesive, for example, an ultraviolet-curing adhesive and an electron beam-curing adhesive can be cited. In addition, from the viewpoint of the curing mechanism, as the active energy ray-curing adhesive, for example, a free radical-curing adhesive, a cation-curing adhesive, an anion-curing adhesive, and a mixture of a free radical-curing adhesive and a cation-curing adhesive can be cited. Representatively, a free radical-curing ultraviolet-curing adhesive can be used. Because of its excellent versatility and easy adjustment of characteristics.
[0142] The adhesive typically contains a curing component and a photopolymerization initiator. As a curing component, a monomer and / or oligomer having a functional group such as a (meth) acrylate group and a (meth) acrylamide group can be cited as a representative example. As a specific example of a curing component, tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, phenoxydiethylene glycol acrylate, cyclic trimethylolpropane formal acrylate, dioxanediol diacrylate, EO modified diglycerol tetraacrylate, γ-butyrolactone acrylate, acryloyl morpholine, unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone, N-methylpyrrolidone, hydroxyethyl acrylamide, N-hydroxymethyl acrylamide, N-methoxymethyl acrylamide, N-ethoxymethyl acrylamide can be cited. These curing components can be used alone or in combination of two or more.
[0143] The adhesive may contain a curing component having a heterocyclic ring. Examples of the curing component having a heterocyclic ring include acryloylmorpholine, γ-butyrolactone acrylate, unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone, and N-methylpyrrolidone.
[0144] The adhesive may further contain an oligomer component in addition to the above-mentioned curing component. By using an oligomer component, the viscosity of the adhesive before curing can be reduced and the workability can be improved. As a representative example of the oligomer component, a (meth)acrylic oligomer can be cited. Examples of the (meth)acrylic monomer constituting the (meth)acrylic oligomer include (meth)acrylic acid (carbon number 1 to 20) alkyl esters, (meth)acrylic acid cycloalkyl esters (e.g., cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, etc.), (meth)acrylic acid aralkyl esters (e.g., benzyl (meth)acrylate, etc.), polycyclic (meth)acrylates (e.g., 2-isobornyl (meth)acrylate, 2-norbornyl methyl (meth)acrylate, 5-norbornene-2-yl-methyl (meth)acrylate, 3-methyl-2-norbornyl methyl (meth)acrylate, etc.), hydroxyl group-containing (meth)acrylates (e.g., hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2,3-dihydroxypropylmethyl-butyl (meth)methacrylate, etc.), alkoxy group-containing or Phenoxy (meth)acrylates (2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-methoxymethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phenoxyethyl (meth)acrylate, etc.), epoxy-containing (meth)acrylates (for example, glycidyl (meth)acrylate, etc.), halogen-containing (meth)acrylates (for example, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,2-trifluoroethylethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropentyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, etc.), alkylaminoalkyl (meth)acrylates (for example, dimethylaminoethyl (meth)acrylate, etc.). Specific examples of (meth)acrylic acid (carbon number 1 to 20) alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, 2-methyl-2-nitropropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, tert-pentyl (meth)acrylate, 3-pentyl (meth)acrylate, 2,2-dimethylbutyl (meth)acrylate, n-hexyl (meth)acrylate, cetyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 4-methyl-2-propylpentyl (meth)acrylate, and n-octadecyl (meth)acrylate. These (meth)acrylates may be used alone or in combination of two or more.
[0145] As the photopolymerization initiator, a photopolymerization initiator known in the art can be used in an amount known in the art, and thus a detailed description thereof will be omitted.
[0146] The tensile modulus of the adhesive layer can be adjusted to a desired value by adjusting the type and amount of the curing component and the photopolymerization initiator.
[0147] The thickness of the adhesive layer (after curing) is typically 0.1 μm to 5 μm, preferably 0.2 μm to 4 μm, and more preferably 0.3 μm to 3 μm.
[0148] A-7. Hard coating
[0149] The hard coat layer 70 can be formed typically by applying a hard coat layer-forming composition containing a curing component and a photopolymerization initiator onto the second main surface side surface of the first retardation layer and curing the composition.
[0150] As a representative example of the hardening component, active energy ray hardening type (meth) acrylate can be cited. As active energy ray hardening type (meth) acrylate, for example, ultraviolet hardening type (meth) acrylate and electron beam hardening type (meth) acrylate can be cited. Ultraviolet hardening type (meth) acrylate is preferred. This is because the hard coating layer can be efficiently formed by simple processing operations.
[0151] UV-curable (meth)acrylates include UV-curable monomers, oligomers, polymers, and the like. UV-curable (meth)acrylates include monomer components and oligomer components having preferably 2 or more, more preferably 3 to 6 UV-polymerizable functional groups. Specific examples of UV-curable (meth)acrylates include urethane acrylates, pentaerythritol triacrylate, ethoxylated glycerol triacrylate, and polyether urethane diacrylate. In addition to these, the curing components of the active energy ray-curable adhesive described in Item A-6 may also be used. The curing components may be used alone or in combination of two or more. The curing method may be a free radical polymerization method or a cationic polymerization method. In one embodiment, an organic-inorganic hybrid material obtained by combining silica particles, polysilsesquioxane compounds, and the like in (meth)acrylates may also be used. The constituent materials and formation method of the hard coat layer are described in, for example, Japanese Patent Application Laid-Open No. 2011-237789, Japanese Patent Application Laid-Open No. 2020-064236, Japanese Patent Application Laid-Open No. 2010-152331, etc. The descriptions of these publications are incorporated herein by reference.
[0152] As the photopolymerization initiator, a photopolymerization initiator known in the art can be used in an amount known in the art, and thus a detailed description thereof will be omitted.
[0153] The tensile modulus of the hard coat layer can be adjusted to a desired value by adjusting the type and amount of the curing component and the photopolymerization initiator.
[0154] The thickness of the hard coat layer is, for example, 0.1 μm to 5 μm, preferably 0.2 μm to 4 μm, and more preferably 0.3 μm to 3 μm.
[0155] A-8. Adjacent layers
[0156] As described above, the adjacent layer is a layer that is adjacent to the second main surface 100b side of the first phase difference layer 30 in a manner that is in direct contact. In one embodiment, the adjacent layer is an adhesive layer 40 provided to bond the first phase difference layer 30 to the second phase difference layer 50. In other embodiments, the adjacent layer is a hard coating layer formed on the second main surface 100b side surface of the first phase difference layer 30.
[0157] The tensile modulus of the adjacent layer at 110°C is 1 MPa or more, typically 10 MPa or more, preferably 20 MPa or more, more preferably 20 MPa to 100 GPa, and further preferably 20 MPa to 10 GPa. By providing a layer having such a tensile modulus of elasticity in close contact with the first phase difference layer, it can help to suppress the thermal shrinkage of the first phase difference layer under high temperature and high humidity. As a result, the generation of cracks in the first phase difference layer can be suppressed, and the outflow of iodine and antistatic agents to the image display panel can also be suppressed.
[0158] The tensile modulus of the adjacent layer at 23°C is preferably 10 MPa or more, more preferably 20 MPa or more, and further preferably 20 MPa to 100 GPa. By providing a layer having such a tensile modulus of elasticity in close contact with the first phase difference layer, it can help to suppress the thermal shrinkage of the first phase difference layer under high temperature and high humidity. As a result, the generation of cracks in the first phase difference layer can be suppressed, and the outflow of iodine and antistatic agents to the image display panel can also be suppressed.
[0159] A-9. Release liner
[0160] As the release liner, for example, a flexible plastic film can be cited. As the plastic film, for example, a polyethylene terephthalate film, a polyethylene film, a polypropylene film, and a polyester film can be cited. The thickness of the release liner is, for example, 3 μm or more, and, for example, 200 μm or less. The surface of the release liner is coated with a release agent. As specific examples of the release agent, a silicone-based release agent, a fluorine-based release agent, and a long-chain alkyl acrylate-based release agent can be cited.
[0161] B. Method for manufacturing polarizing plate with phase difference layer
[0162] The polarizer with a phase difference layer described in item A can be manufactured by a manufacturing method comprising the following steps: (Step 1) laminating the polarizer and the first phase difference layer via the first adhesive layer; (Step 2) laminating the first phase difference layer and the second phase difference layer via the adhesive layer; and (Step 3) providing a second adhesive layer on the side of the second phase difference layer opposite to the side where the first phase difference layer is provided. The order of steps 1 to 3 is not particularly limited. For example, the first phase difference layer and the second phase difference layer can be laminated via an adhesive layer to produce a laminate (step 2), the laminate is laminated to the polarizer via the first adhesive layer (step 1), and the second adhesive layer is laminated on the polarizer with a phase difference layer thus obtained (step 3). The adhesive layer can be formed by applying an adhesive to any adherend, laminating another adherend on the coating layer, and then irradiating it with active energy rays. The irradiation conditions can be appropriately set according to the composition and purpose of the adhesive.
[0163] C. Image display device
[0164] The polarizing plate with a phase difference layer described in item A can be applied to an image display device. Therefore, the embodiment of the present invention also includes an image display device having such a polarizing plate with a phase difference layer. As representative examples of image display devices, liquid crystal display devices and organic EL display devices can be cited. The image display device of the embodiment of the present invention is, for example, Figure 3 As shown in , it has an image display panel 200 such as a liquid crystal panel, an organic EL panel, and a polarizer 100 with a phase difference layer recorded in item A arranged on the visible side of the image display panel 200. At this time, the polarizer 100 with a phase difference layer is bonded to the image display panel 200 via the second adhesive layer in such a way that the second main surface 100b becomes the image display panel 200 side. In addition, the image display panel 200 typically includes electrodes for driving or touch sensors of display elements (including a conductive layer of a laminated structure of an Al layer and a Ti layer, etc.) on its surface and / or inside. In one embodiment, the resistivity change of the electrode after the image display device is maintained at 110°C 85% RH for 36 hours (resistivity after maintenance / resistivity before maintenance) is less than 2, preferably less than 1.8, more preferably less than 1.5, and further preferably less than 1.2.
[0165] Example
[0166] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. Unless otherwise specified, "parts" and "%" in the examples and comparative examples are by weight.
[0167] <Thickness>
[0168] The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL Ltd., product name “JSM-7100F”). The thickness exceeding 10 μm was measured using a digital micrometer (manufactured by ANRITSU Ltd., product name “KC-351C”).
[0169] <Tensile elastic modulus>
[0170] The tensile modulus was calculated from the linear regression of the stress-strain curve obtained by performing a tensile test at 23°C or 110°C in accordance with JIS K 7127. The tensile test was performed by cutting the adhesive layer formed so as to have a thickness of 1 mm into a strip with a width of 10 mm to prepare a sample for measurement, and inserting 20 mm at each end of the sample for measurement into the chucks of a universal tensile testing machine, and the test was performed under the conditions of a chuck distance of 60 mm and a tensile speed of 150 mm / min.
[0171] <Storage elastic modulus>
[0172] A plurality of pressure-sensitive adhesive layers were stacked to a thickness of about 1.5 mm, and dynamic viscoelasticity was measured under the following conditions using the Advanced Rheometric Expansion System (ARES) manufactured by Rheometric Scientific Co., Ltd. The storage elastic modulus at 23° C. or 110° C. was read from the measurement results.
[0173] (Measurement conditions)
[0174] Deformation mode: Twist
[0175] Measuring frequency: 1Hz
[0176] Heating rate: 5℃ / min
[0177] Measuring temperature: -50~150℃
[0178] Shape: parallel plate 8.0mmφ
[0179] <Surface resistivity>
[0180] Regarding the adhesive layer containing an antistatic agent in the first adhesive layer and the second adhesive layer used in the preparation of the polarizer with a phase difference layer, the surface resistivity was measured using a high resistance resistivity meter (Mitsubishi Chemical Analytech, HIRESTA MCP-HT450) after being placed in the state of a laminate of [release liner / adhesive layer] in a room (temperature 25±5°C, relative humidity 50±10%) for 1 minute. It should be noted that for Comparative Example 2, the surface resistivity of both the first adhesive layer and the second adhesive layer was measured in the same manner as described above. The upper limit of the surface resistivity measurement is 1×10 14 Ω / sq.
[0181] [Manufacturing Example 1: Polarizing Plate]
[0182] As the thermoplastic resin substrate, a long amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) having a Tg of about 75° C. was used, and one surface of the resin substrate was subjected to a corona treatment.
[0183] 13 parts by weight of potassium iodide was added to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER") in a ratio of 9:1, and the resulting substance was dissolved in water to prepare a PVA aqueous solution (coating solution).
[0184] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a PVA-based resin layer having a thickness of 13 μm, thereby producing a laminate.
[0185] The obtained laminate was uniaxially stretched to 2.4 times in the longitudinal direction (length direction) in an oven at 130° C. (in-air auxiliary stretching treatment).
[0186] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).
[0187] Next, the film was immersed in a dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide at a weight ratio of 1:7 per 100 parts by weight of water) at a liquid temperature of 30° C. for 60 seconds while adjusting the concentration so that the single body transmittance (Ts) of the polarizer finally obtained becomes a desired value (dyeing treatment).
[0188] Next, the sample was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).
[0189] Afterwards, the laminate was immersed in an aqueous boric acid solution (boric acid concentration 4 wt%, potassium iodide concentration 5 wt%) at a liquid temperature of 70°C, and was uniaxially stretched (underwater stretching treatment) in the longitudinal direction (length direction) between rollers with different peripheral speeds so that the total stretching ratio became 5.5 times.
[0190] Thereafter, the laminate was immersed in a washing bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (washing treatment).
[0191] Thereafter, the sheet was brought into contact with a SUS heating roll whose surface temperature was maintained at about 75° C. while being dried in an oven maintained at about 90° C. (drying shrinkage treatment).
[0192] In this manner, a polarizer having a thickness of about 5 μm was formed on the resin substrate.
[0193] On the surface of the obtained polarizer (the surface on the opposite side from the resin substrate), an HC-TAC film (first protective layer) as a protective layer is bonded via an ultraviolet curing adhesive. Specifically, the curing adhesive is applied in a manner to have a thickness of 1.0 μm, and bonding is performed using a rolling mill. Thereafter, UV rays are irradiated from the protective layer side to cure the adhesive. It should be noted that the HC-TAC film is a film having a hard coating (HC) layer (7 μm thick) formed on a triacetylcellulose (TAC) film (25 μm thick), and is bonded in a manner such that the TAC film becomes the polarizer side.
[0194] 97.0 parts of methyl methacrylate (MMA, manufactured by FUJIFILM Wako Pure Chemical Corporation, trade name "methyl methacrylate monomer"), 3.0 parts of a comonomer represented by the following formula (1e), and 0.2 parts of a polymerization initiator (manufactured by FUJIFILM Wako Pure Chemical Corporation, trade name "2,2′-azobis(isobutyronitrile)") were dissolved in 200 parts of toluene. Subsequently, a polymerization reaction was carried out for 5.5 hours while heating to 70°C under a nitrogen atmosphere to obtain a boron-containing acrylic resin solution (solid content concentration: 33%). The obtained boron-containing acrylic polymer had a Tg of 110°C and an Mw of 80,000. 20 parts of the obtained boron-containing acrylic resin were dissolved in 80 parts of methyl ethyl ketone to obtain a resin solution (20%).
[0195] The resin substrate was peeled off from the polarizer, and the resin solution was applied to the peeled surface using a wire rod, and the coated film was dried at 60° C. for 5 minutes to form a second protective layer (thickness 400 nm) consisting of a cured product of the coated film of the organic solvent solution of the resin. Thus, a polarizing plate having a structure of [TAC film with HC layer (first protective layer) / polarizer / cured layer of boron-containing acrylic resin (second protective layer)] was obtained.
[0196] [Chemical formula 3]
[0197]
[0198] [Manufacturing Example 2: First Phase Difference Layer]
[0199] In a batch polymerization apparatus comprising two vertical reactors equipped with stirring blades and a reflux cooler controlled at 100° C., 29.60 parts by weight (0.046 mol) of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane, 29.21 parts by weight (0.200 mol) of isosorbide (ISB), 42.28 parts by weight (0.139 mol) of spiroglycol (SPG), 63.77 parts by weight (0.298 mol) of diphenyl carbonate (DPC) and 1.19×10 mol of calcium acetate monohydrate as a catalyst were charged. -2 Weight parts (6.78×10 - 5 mol). After the reactor is replaced with nitrogen under reduced pressure, it is heated with a heat medium and stirring is started when the internal temperature reaches 100°C. After 40 minutes from the start of heating, the internal temperature reaches 220°C and is controlled to maintain this temperature. At the same time, the pressure is reduced and set to 13.3kPa after reaching 220°C for 90 minutes. The phenol vapor produced as a by-product of the polymerization reaction is introduced into a reflux cooler at 100°C, and a certain amount of monomer components contained in the phenol vapor is returned to the reactor. The uncondensed phenol vapor is introduced into a condenser at 45°C and recovered. After nitrogen is introduced into the first reactor and the pressure is temporarily restored to atmospheric pressure, the oligomerized reaction liquid in the first reactor is transferred to the second reactor. Next, the temperature and pressure reduction in the second reactor are started, and the internal temperature is set to 240°C and the pressure is 0.2kPa in 50 minutes. After that, polymerization is carried out until the specified stirring power is reached. When a predetermined power was reached, nitrogen was introduced into the reactor to restore the pressure, and 0.7 parts by weight of PMMA was melt-kneaded with 100 parts by weight of the produced polyester carbonate resin, and extruded into water. The strands were cut to obtain pellets.
[0200] The obtained polyester carbonate resin (pellets) was vacuum dried at 80°C for 5 hours, and then a film-making device equipped with a single screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder setting temperature: 250°C), a T-die (width 200mm, setting temperature: 250°C), a chill roll (setting temperature: 120-130°C) and a winder was used to prepare a long strip of resin film with a thickness of 105 μm. The obtained long strip of resin film was adjusted in a manner to obtain a predetermined phase difference while being stretched 2.8 times in the width direction at 138°C to obtain a phase difference film with a thickness of 38 μm. The obtained phase difference film had a Re(550) of 144 nm and a Re(450) / Re(550) of 0.86.
[0201] [Manufacturing Example 3: Second Phase Difference Layer]
[0202] A liquid crystal coating liquid was prepared by dissolving 20 parts by weight of a side chain liquid crystal polymer represented by the following chemical formula (3) (the numbers 65 and 35 in the formula represent the molar % of the monomer unit, and for convenience, the block polymer is expressed as a weight average molecular weight of 5000), 80 parts by weight of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure 907) in 200 parts by weight of cyclopentanone. Then, the coating liquid was applied to a PET substrate subjected to a vertical alignment treatment using a bar coater, and then heated and dried at 80° C. for 4 minutes to orient the liquid crystal. The liquid crystal layer was irradiated with ultraviolet rays to cure the liquid crystal layer, thereby forming a liquid crystal orientation solidified layer (thickness 3 μm) exhibiting a refractive index characteristic of nz>nx=ny on the substrate.
[0203] [Chemical formula 4]
[0204]
[0205] [Manufacturing Example 4A: Adhesive]
[0206] 5 parts by weight of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., trade name "KBM-303"), 35 parts by weight of 4-hydroxybutyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd.), 24 parts by weight of neopentyl glycol diacrylate (manufactured by Kyoeisha Chemical Co., Ltd., trade name "LIGHT ACRYLATE NP-A"), 10 parts by weight of isocyanuric acid EO-modified triacrylate (manufactured by Toagosei Co., Ltd., trade name "Aronix M-315"), 5 parts by weight of pentaerythritol triacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., trade name "A-TMM-3LM-N"), 15 parts by weight of polyurethane acrylic oligomer (manufactured by Mitsubishi Chemical Co., Ltd., trade name "UV3000B"), 3 parts by weight of photopolymerization initiator (manufactured by IGM Resins, trade name "Omnirad 184”), 2 parts by weight of a photopolymerization initiator (manufactured by San-Apro, trade name “CPI-100P”) and 1 part by weight of boric acid (manufactured by FUJIFILM Wako Pure Chemical Corporation) were mixed and stirred for 3 hours to obtain an active energy ray-curable adhesive 4A.
[0207] [Manufacturing Example 4B: Adhesive]
[0208] 20 parts by weight of acryloylmorpholine (manufactured by Kojin Co., Ltd., trade name: ACMO), 50 parts by weight of unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone (manufactured by Daicel Co., Ltd., trade name: PLACCEL FA1DDM), 10 parts by weight of PEG400# diacrylate (manufactured by Kyoeisha Chemical Co., Ltd., trade name: LIGHT ACRYLATE 9EG-A), 15 parts by weight of a copolymer oligomer of butyl acrylate and methacrylate in a molar ratio of 34 / 66 (manufactured by Toagosei Co., Ltd., trade name: ARUFONUP-1190), 3 parts by weight of 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one (photopolymerization initiator) (manufactured by IGM Resins Co., Ltd., trade name: Omnirad 907) and 2 parts by weight of diethylthioxanthone (photopolymerization initiator) (manufactured by Nippon Kayaku Co., Ltd., trade name: KAYACURE DETX-S) and stirred for 3 hours to obtain an active energy ray-curable adhesive 4B.
[0209] [Manufacturing Examples 5A-5H: Adhesive Layer]
[0210] 1. Synthesis of (meth)acrylic acid polymers
[0211] Into a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube and a cooler, monomer components were added so as to have the composition described in Table 1, and then a polymerization initiator was added. After nitrogen was introduced while slowly stirring to replace the inside of the flask with nitrogen, the liquid temperature in the flask was maintained at about 55° C., and a polymerization reaction was performed for 7 hours. Then, ethyl acetate was added to the obtained reaction solution to adjust the solid content concentration to 12% by weight, to obtain solutions of (meth)acrylic polymers 5A to 5H.
[0212] [Table 1]
[0213]
[0214] BA:Butyl acrylate PEA:2-phenoxyethyl acrylate
[0215] AA: Acrylic acid MA: Methyl acrylate
[0216] HBA: 4-Hydroxybutyl acrylate DMA: 2-(Dimethylamino)ethyl methacrylate
[0217] HEA: 2-Hydroxyethyl Acrylate MEA: 2-Methoxyethyl Acrylate
[0218] ACMO: Acryloylmorpholine
[0219] BzA:Benzyl acrylate
[0220] NVP: N-vinyl pyrrolidone
[0221] 2. Preparation of Adhesive
[0222] Adhesives 5A to 5H were obtained by mixing a crosslinking agent and, if necessary, a silane coupling agent and / or an antistatic agent in a solution of (meth)acrylic polymers 5A to 5H so that the amount thereof was the value shown in Table 2 relative to 100 parts by weight of the solid content of the (meth)acrylic polymer. In the table, LiTFSi is lithium bis(trifluoromethanesulfonyl)imide, EMP-TFSi is ethylmethylpyrrolidinium bis(trifluoromethanesulfonyl)imide, TBMA-TFSi is tributylmethylammonium bis(trifluoromethanesulfonyl)imide, and MOPy-PF6 is methyloctylpyridinium hexafluorophosphate.
[0223]
[0224] 3. Formation of adhesive layer
[0225] Adhesives 5A to 5H were applied to the release surface of a release liner having a silicone treatment, i.e., a 38 μm thick PET film (MRF38 manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.), and then dried in an air-circulating constant temperature oven set at a specified temperature to form adhesive layers 5A to 5H having a specified thickness.
[0226] [Example 1]
[0227] The adhesive layer 5A (5 μm thick) obtained in Manufacturing Example 5A was transferred from the release liner to the surface of the second protective layer of the polarizer obtained in Manufacturing Example 1, and the first phase difference layer obtained in Manufacturing Example 2 was bonded to the polarizer via the adhesive layer 5A to obtain a laminate. At this time, the first phase difference layer was arranged so that the slow axis formed an angle of 45° with respect to the absorption axis of the polarizer.
[0228] The active energy ray-curable adhesive obtained in Manufacturing Example 4A was applied to one side of the second phase difference layer obtained in Manufacturing Example 3 using an MCD coater (manufactured by Fuji Machinery Co., Ltd.) so that the thickness after curing was 1 μm, and then bonded to the surface of the first phase difference layer of the above-mentioned laminate by a rolling mill. Thereafter, the active energy ray irradiation device was used from the second phase difference layer side so that the accumulated light amount was 4500 mJ / cm 2 After the adhesive was cured by irradiating with ultraviolet rays, it was dried with hot air at 70°C for 3 minutes.
[0229] The adhesive layer 5E (thickness 20 μm) obtained in Manufacturing Example 5E is transferred from the release liner to the surface of the second phase difference layer of the stacked body obtained by the above operation, thereby obtaining a polarizer with a phase difference layer having the structure of [polarizer / first adhesive layer (adhesive layer 5A) / first phase difference layer / adhesive layer (hardened layer of adhesive 4A) / second phase difference layer / second adhesive layer (adhesive layer 5E)].
[0230] [Examples 2 to 4, Comparative Examples 1 to 5]
[0231] In Examples 2 to 4 and Comparative Examples 3 to 5, except that the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer were changed as shown in Table 3, the same procedure as in Example 1 was carried out to obtain polarizing plates with retardation layers.
[0232] In addition, in Comparative Examples 1 and 2, the first adhesive layer, the adhesive layer and the second adhesive layer were changed as shown in Table 3, and after the first phase difference layer was bonded to the polarizer, the adhesive shown in Manufacturing Example 4B was applied to the surface of the first phase difference layer and then the second phase difference layer was bonded. The same operation as in Example 1 was performed to obtain a polarizer with a phase difference layer. Ultrathin slices were made from the obtained polarizer with a phase difference layer and TEM observation was performed. As a result, a compatible region with a thickness of about 100 nm was formed on the adhesive layer side of the first phase difference layer. The compatible region can be formed using an acrylic monomer shown in the adhesive shown in Manufacturing Example 4B, especially acryloyl morpholine (manufactured by Xingren Co., Ltd., trade name: ACMO).
[0233] The following properties were evaluated about the polarizing plates with retardation layers obtained in Examples and Comparative Examples.
[0234] 1. Resistivity of sensor electrodes in wet heat test
[0235] A test body for evaluating the resistivity of the touch sensor electrode of the assumed touch panel was prepared. Specifically, an Al-deposited film (manufactured by Toray Industries, product number "DMS-X42G") having an aluminum-deposited layer (thickness 0.05 μm) on one side of a PET resin film (thickness 50 μm) was cut into a length of 70 mm and a width of 150 mm, and the PET resin film surface was bonded to a glass plate via an acrylic adhesive layer to prepare a glass plate with an Al-deposited layer having a structure of [aluminum-deposited layer / resin film / glass plate]. The polarizer with a phase difference layer prepared in the embodiment and the comparative example was cut into a length of 70 mm and a width of 150 mm, and the ends in the length direction and the width direction were aligned and laminated via the second adhesive layer and the aluminum-deposited layer of the glass plate with the Al-deposited layer. Thus, a test body for resistivity evaluation was obtained. The test body was placed in a heated and humidified atmosphere at a temperature of 110°C and a relative humidity of 85% for 36 hours. Next, the test body was returned to an atmosphere of 25°C and 50% relative humidity, and the surface resistivity (Ω / sq) of the aluminum vapor-deposited layer was measured using EC-80 (non-contact resistance measuring instrument) manufactured by NAPSON. The value obtained by dividing the surface resistivity after the wet heat test by the surface resistivity before the test is shown in Table 3 as "Sensor electrode resistivity change".
[0236] 2. Cracks in wet heat test
[0237] The polarizer with a phase difference layer obtained in the examples and comparative examples was cut into a size of 7 cm in width × 15 cm in length. The cut polarizer with a phase difference layer was bonded to a glass plate via a second adhesive layer, and the glass plate was also bonded to the polarizer side via an acrylic adhesive to prepare a sample to be tested having a structure of [glass plate / polarizer with a phase difference layer / glass plate].
[0238] The sample to be tested was subjected to a damp heat test in an atmosphere of a temperature of 110° C. and a relative humidity of 85% for 36 hours.
[0239] The samples after the wet heat test were observed under a microscope and evaluated according to the following criteria. The results are shown in Table 3.
[0240] ○: No cracks penetrating the first retardation layer in the thickness direction were generated
[0241] ×: A crack has occurred that penetrates the first phase difference layer in the thickness direction.
[0242]
[0243] As shown in Table 3, the polarizer with phase difference layer of the embodiment can maintain the antistatic function sufficient for practical use and can suppress the adverse effects on the image display panel under high temperature and high humidity. On the other hand, the polarizer with phase difference layer of Comparative Examples 1 and 2 has a large change in sensor electrode resistivity after the wet heat test. It is speculated that this is because the tensile elastic modulus of the adhesive layer adjacent to the first phase difference layer at 23°C is 2.6×10 6 As shown in Figure 1, the tensile modulus at 110°C is less than 1 MPa, resulting in insufficient suppression of cracks in the first phase difference layer, which results in outflow of iodine or antistatic agent. In addition, in the polarizing plates with phase difference layers of Comparative Examples 3 to 5, the change in resistivity of the sensor electrode after the wet heat test is also greater than 2, but it is speculated that this is due to corrosion of the electrode layer (Al layer) caused by the antistatic agent contained in the adhesive layer.
[0244] Industrial Applicability
[0245] The laminated body according to the embodiment of the present invention can be used, for example, for the production of a polarizing plate with a retardation layer used in an image display device. Representative examples of image display devices include liquid crystal display devices, organic EL display devices, and inorganic EL display devices.
[0246] Explanation of symbols
[0247] 10 Polarizer
[0248] 12 Polarizer
[0249] 14 Protective layer
[0250] 20 1st adhesive layer
[0251] 301st phase difference layer
[0252] 40 adhesive layers
[0253] 50 2nd phase difference layer
[0254] 60 Second adhesive layer
[0255] 70 Hard coating
[0256] 100 Polarizing film with phase difference layer
[0257] 200 Image display panel
[0258] 300 Image display device
Claims
1. A polarizing plate with a phase difference layer, comprising a first main surface and a second main surface facing each other, The film includes, in order from the first main surface toward the second main surface, a polarizing plate including a polarizer, a first adhesive layer, a first phase difference layer, an adhesive layer, a second phase difference layer, and a second adhesive layer, The polarizing plate with a phase difference layer comprises an adhesive layer containing an antistatic agent. The tensile modulus of elasticity of the adjacent layer of the first retardation layer adjacent to the second main surface side at 110° C. is 1 MPa or more. The amount of the antistatic agent added to the adhesive layer containing the antistatic agent is 5 phr or less. When the polarizer with a phase difference layer is bonded to the aluminum layer surface of a laminate comprising a polyethylene terephthalate resin film with a thickness of 50 μm and an aluminum layer with a thickness of 0.05 μm arranged on one surface thereof via the second adhesive layer, the resistivity of the aluminum layer changes to less than 2 after being maintained at 110°C and 85% RH for 36 hours.
2. The polarizing plate with a phase difference layer according to claim 1, wherein: The first phase difference layer is a stretched film of a resin film. The Re(550) of the first retardation layer is 100 nm to 190 nm, and the Re(450) / Re(550) is 0.8 or more and less than 1. The angle formed between the slow axis of the first phase difference layer and the absorption axis of the polarizer is 40° to 50°.
3. The polarizing plate with a phase difference layer according to claim 1, wherein: The first retardation layer has a thickness of 10 μm or more.
4. The polarizing plate with a phase difference layer according to claim 2, wherein: The second retardation layer exhibits a refractive index characteristic of nz>nx=ny.
5. The polarizing plate with a phase difference layer according to claim 1, wherein: The surface resistivity of the first adhesive layer and / or the second adhesive layer is 9×10 11 Ω / sq or less.
6. The polarizing plate with a phase difference layer according to claim 1, wherein: The antistatic agent includes an ionic compound containing bistrifluoromethanesulfonimide as an anion.
7. The polarizing plate with a phase difference layer according to claim 1, wherein: The adjacent layer is the adhesive layer.
8. The polarizing plate with a phase difference layer according to claim 1, wherein: The adjacent layer is a hard coating layer formed directly on the second main surface side of the first retardation layer. 9 . An image display device comprising an image display panel and the polarizing plate with a retardation layer according to claim 1 , which is arranged on a viewing side of the image display panel.
10. The image display device according to claim 9, wherein: The image display panel comprises electrodes, The resistivity of the electrode after being kept at 110° C. and 85% RH for 36 hours changed to 2 or less.
